If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + x + -2 = 3x Reorder the terms: -2 + 4x + x = 3x Combine like terms: 4x + x = 5x -2 + 5x = 3x Solving -2 + 5x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -2 + 5x + -3x = 3x + -3x Combine like terms: 5x + -3x = 2x -2 + 2x = 3x + -3x Combine like terms: 3x + -3x = 0 -2 + 2x = 0 Add '2' to each side of the equation. -2 + 2 + 2x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 2x = 0 + 2 2x = 0 + 2 Combine like terms: 0 + 2 = 2 2x = 2 Divide each side by '2'. x = 1 Simplifying x = 1
| 5x+7=x+31 | | 4w+18=54 | | 3t-5=28 | | 9s-4=32 | | 6-5p=-19 | | 7+3y=19 | | 4y=-88 | | r^2-2r+10=0 | | 18=2xn | | x^2-x-414=0 | | 9x+18x-x-2= | | 2x^4-8x^3+3x^2-12x=0 | | -2(5-2x)=8(2x+1) | | (2x-4x)+14+24x=16 | | t^2=4t | | (c^2+8c+19)=0 | | 6x+3=5-2(4+-1) | | x^2+12x+6=-5 | | 4y=2y+18 | | y=0.4x^2+5.4x+14.8 | | x^2-11001x-462000=0 | | c^2-9c+8= | | X^2-kx+36=0 | | m^2-m=0 | | 5-8x=86-29x | | -23-6x=8x+24 | | 9x-3=16x-43 | | 0.03p-0.12=-0.01p | | 80=3a+2y | | -3.9x-1=-3.7x+3 | | 5d^2-100=0 | | 2n+3.6=6.8 |